Thermoluminescence and phototransferred phermoluminescence of synthetic quartz - Dawam, Robert Rangmou (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2020)
The main aim of this investigation is on thermoluminescence and phototransferred thermoluminescence of synthetic quartz. Thermoluminescence was one of the tools used in characterising the electron traps parameters. The samples of quartz annealed at various temperatures up to 900ÌŠC and the unannealed were used. The thermoluminescence glow curve was measured at 1ÌŠC s~ 1 following beta irradiation to 40 Gy from the samples annealed at 500ÌŠC and the unannealed consist of main peak at 70ÌŠC and secondary peaks at 110, 180 and 310ÌŠC. In comparison, the thermoluminescence glow curve for the sample annealed at 900ÌŠC have main peak at 86ÌŠC and the secondary ones at 170 and 310ÌŠC. The kinetic analysis was carried out only on the main peak in each case. The activation energy was found to be decreasing with increase in annealing temperatures. The samples annealed at 500ÌŠC and the unannealed were found to be affected by thermal quenching while sample annealed at 900ÌŠC shows an inverse quenching for irradiation dose of 40 Gy. However, when the dose was reduce to 3 Gy the effects of thermal quenching was manifested. The activation energy of thermal quenching was also found to decrease with increase in annealing temperature. Thermally assisted optically stimulated luminescence measurement was carried out using continuous wave optical stimulated luminescence (CW-OSL). The samples studied were those annealed at 500ÌŠC for 10 minutes, 900ÌŠC for 10, 30, 60 minutes and 1000ÌŠC for 10 minutes prior to use. The CW-OSL is stimulated using 470 nm blue LEDs at sample temperatures between 30 and 200ÌŠC. It is measured after preheating to either 300 and 500ÌŠC. When the integrated OSL intensity is plotted as a function of measurement temperature, the intensity goes through a peak. The increase in OSL intensity as a function of temperature is associated to thermal assistance and the decrease to thermal quenching. The kinetic parameters were evaluated by fitting the experimental data. The values of activation energies of thermal quenching are the same within experimental uncertainties for all the experimental conditions. This shows that annealing temperature, duration of annealing and irradiation dose have a negligible influence on the recombination site of luminescence using OSL. Phototransferred thermoluminescence (PTTL) induced from annealed samples using 470 nm blue light was also investigated. The quartz were annealed at 500 _C for 10 minutes, 900ÌŠC for 10, 30, 60 minutes and 1000ÌŠC for 10 minutes prior to use. The glow curves of conventional TL measured at 1 _C sô€€€1 following irradiation to 200 Gy shows six peaks in each case labelled I-VI for ease of reference whereas peaks observed under PTTL are referred to as A1 onwards. Only the first three peaks were reproduced under phototransfer for the sample annealed at 900ÌŠC for 60 minutes and 1000ÌŠC C for 10 minutes. Interestingly, for the intermediate duration of annealing of 30 minutes, the only peak that appears under phototransfer is the A1. For quartz annealed at 900ÌŠC for 10 minutes, the PTTL appears as long as the preheating temperature does not exceed 560ÌŠC. All other annealing temperatures, PTTL only appears for preheating to 450 and below. This shows that the occupancy of deep electron traps at temperatures beyond 450ÌŠC or 560ÌŠC is low. The activation energy for peaks A1, A2 and A3 were calculated. The PTTL peaks were studied for thermal quenching and peaks A1 and A3 were found to be affected. The activation energies for thermal quenching were determined as 0.62 Â± 0.04 eV and 0.65 Â± 0.02 eV for peaks A1 and A3 respectively. The experimental dependence of PTTL intensity on illumination time is modelled using sets of coupled linear differential equations based on systems of donors and acceptors whose number is determined by preheating temperature.
Keywords: Thermoluminescence; Quartz